PENGARUH RELIGIUSITAS TERHADAP TINGKAT DEPRESI, KECEMASAN, STRES, DAN KUALITAS HIDUP PENDERITA PENYAKIT KRONIS DI KOTA MAKASSAR (KAJIAN SURVEI EPIDEMIOLOGI BERBASIS INTEGRASI ISLAM DAN KESEHATAN) - M. Fais Satrianegara (Jurnal Kesehatan, 2014)
In Indonesia, according to source of Riskersda in 2007, the most powerful of death cause was stoke (15,4%), then hypertensi, diabet, cancer and cronic and obstructif lungs dis-ease which can decrease the grand quality of life. There were many studies that told us reli-giousity (obeying the religion‟s rule) had good impact for health, one example was in US.This research purpose is to tell us the relationship between religiousity and depression, anxiety, stress and life quality of cronic sufferer in Makassar, which is held in Haji Hospital and Labuang Baji Hospital. All of cronic sufferer in Makassar 2013 are population which taken by non probability sample accidental sampling total ammount 38 people. This research uses survey analitical method with cross sectional study by using question to get the data about religiousity, depression, anxiety and stress, also patient life quality.The result of this research shows us that, there is no significant relationship between religiousity and depression of cronic disease because mark of P >0,05 is 0,457 and shows positive relations with weak relation 0,321. Religiousity of anxiety also shows there is no sig-nificant relationship between religiousity and anxiety chronic suffer disease because mark of P >0,05 is -0,72 and shows negativecorrelation with strong correlation 0,769. Religiousity of stress shows there is no significant relationship between religiousity and stress of chronic suffer because mark of P>0,05 is 0,232 and shows positive correlation with power of corre-lation 0,449. Besides religiousity and life quality shows there is no significant reltionship be-tween religiousity and life quality of chronic suffer because mark of P>0,05 is 0,556 and shows positive correlationwith weak correlation 0,250.We need new program from the health and medical departement especially the hospital that can include religiousity to the patient in healing process. Applying religiousity research in many side of life, not only in health and medical departement but also ini educational de-partement, then religousity experience especially for the patient in dialy of life by reading and reciting the holy qur‟an.Key word : Cronic disease, religiousity, depression, anxiety, stress and quality of life